Solutions to Improve the Efficiency of Digital Marketing Communication Tools for Hanami Hotel Danang - Pham, Thu Hang (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Digital Marketing; 2021-2025.